Pengaruh Efisiensi dan Efektivitas Terhadap Kinerja Pasar Industri Barang Konsumsi di Indonesia - Kathleen Arlen Manueke (Peneliti.net, 2023)
This research was conducted to examine the effect of efficiency and effectiveness on market performance by using secondary data from companies in the consumer goods industry listed on the Indonesia Stock Exchange in 2014-2018. The results showed that the effectiveness as measured by inventory turnover has a significant positive effect on market performance as measured by the price-earnings ratio. The results of this study indicate that investors in the consumer goods industry in Indonesia consider the effectiveness of companies in inventory management. This shows that investors are willing to take high risks by considering the speed of inventory turnover in the hope of obtaining high profits. Subsequent research can examine the effect of efficiency and effectiveness on the Consumer Goods Industry with a sample of ASEAN countries, research involving other sectors in the manufacturing and trade industries that have inventories such as basic and chemical industries, miscellaneous industry, wholesale and retail trade taking into account economic variables macro such as inflation rate, interest rate and exchange rate